320 Assessment of Medication Prescribing using Test your Care Metrics. (16th September 2019) - Leahy, Aoife; Hynes, Jason; McCarthy, Christine E; Roy, Amrita; Mohd Asri, Nur Atikah; Saif, Kiran; Murphy, Elizabeth; Sebaoui, Salim; Matti, Basil; Gabr, Ahmed; Zulkifli, Muhamad Daniel; Crotty, James; et al.
Abstract: Background: Medication records are essential components of patient care and a source of medical error. The HSE Code of Practice for Healthcare Records Management has highlighted criteria which must be complied with in these records. In the HSE Clinical Strategy and Programmes Division, "Test your care" is used to promote a code of practice and a set of metrics which need to be adhered to. Methods: We reviewed all drug kardexes in 14 wards both medical and surgical in a 48 hour period. We assessed the drug kardexes based on 9 different metrics. (Generic names used, capital letters used, start date recorded, legible dosing, route and frequency of medication documented, minimum dosing documented, legible prescriptions and discontinued drugs crossed off) Results: 285 drug kardexes were reviewed. No drug kardex was fully compliant with the 9 standards. The main deficits were in relation to use of brand names, no documentation of frequency and omission of IMC numbers. The average number of metrics met was lower on surgical wards than medical wards - 3.6 vs 4.7 respectively, and this difference was statistically significant (p< .00001; 2 sample t test). Conclusion: The universal poor compliance with these standards highlights both the poor design of the current drug kardex and poor awareness with prescribers of these standards. In the current drug kardex, there is no dedicated space for frequency or IMC number and therefore these are often forgotten. The use of brand names consistently highlights poor prescribing practice and more education is required to improve this. We plan to improve current prescribing education sessions for all doctors to highlight the current deficiencies and to increase compliance with standards.